Current soccer footwear, its role in injuries and potential for improvement - Blanchard, S.; Palestri, J.; Guer, J.-L.; Behr, M. (Sports Medicine International Open, 2018)
Soccer is the most popular sport in the world and generates great financial revenue. It is also a sport whose practice has evolved considerably in terms of intensity and commitment, and in which the intrinsic risk of injury (not directly related to an interaction with the environment) is particularly high. In this context, the cleated shoe as a major component of soccer equipment may play a key role in the overexposure to injury. Soccer shoe evolution is all the more challenging, because design and mechanical structure differ in many points compared to other modern shoes developed for sports such as running, tennis and basketball.